2022
DOI: 10.1186/s13063-022-06057-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of modified Bushen Yiqi formulas (MBYF) as an add-on to formoterol and budesonide in the management of COPD: study protocol for a multicentre, double-blind, placebo-controlled, parallel-group, randomized clinical trial: FB-MBYF Trial

Abstract: Background Inhaled glucocorticoid corticosteroid (ICS), long-acting β2-adrenoceptor agonist (LABA), and other drugs have limited therapeutic effects on COPD with significant individual differences. Traditional Chinese medicine (TCM)-modified Bushen Yiqi formula (MBYF) demonstrates advantages in COPD management in China. This study aims to evaluate the efficacy and safety of MBYF as an add-on to budesonide/formoterol in COPD patients and confirm the related genes affecting the therapeutic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The rat dose of 12.5 g/kg was calculated as 9.1× human dose. The human dose of 125 g/70 kg is referenced to the clinical dose from our two clinical trials (14,19). Five herbal formulas were dissolved in ultrapure water every three days and stored at 4°C.…”
Section: Mbyf Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The rat dose of 12.5 g/kg was calculated as 9.1× human dose. The human dose of 125 g/70 kg is referenced to the clinical dose from our two clinical trials (14,19). Five herbal formulas were dissolved in ultrapure water every three days and stored at 4°C.…”
Section: Mbyf Preparationmentioning
confidence: 99%
“…Our randomized controlled trials (RCTs) found MBYF-related herbs could bene t patients with COPD and asthma, including reducing pulmonary function decline, decreasing the level of in ammatory cytokines in serum, and improving life quality (12,13). Two RCTs (Trial registration ID: ChiCTR1900026124, ChiCTR1900021907), are carried out to assess the safety and e cacy of MBYF on patients with COPD and asthma (14). As detailed in our previous report (14)(15)(16), MBYF contains ve herbs: Huang Qi, Yin Yang Huo, Di Huang, Huang Qin, and Chi Shao.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It adds Scutellariae radix (Huangqin) and Paeoniae radix rubra (Chishao) to Bushen Yiqi formula (BSYQF), combined with Astragali radix (Huangqi), R. rehmanniae (Dihuang) and Epimedii folium (Yinyanghuo). 14 Chinese medicine has definite pharmacological properties, such as anti-inflammatory, spasmolysis, hemostasis, and phlegm effects. Chinese herbal medicine use is often combined with the patient's excess or deficiency, thus becoming the complex organic that is often used to treat chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Modified Bushen Yiqi formula (MBYF) comprises five Chinese herbal medicines. It adds Scutellariae radix (Huangqin) and Paeoniae radix rubra (Chishao) to Bushen Yiqi formula (BSYQF), combined with Astragali radix (Huangqi), R. rehmanniae (Dihuang) and Epimedii folium (Yinyanghuo) 14 . Chinese medicine has definite pharmacological properties, such as anti‐inflammatory, spasmolysis, hemostasis, and phlegm effects.…”
Section: Introductionmentioning
confidence: 99%